Relationships Between Classical and Shear Deformation Theories of Axisymmetric Circular Plates - Reddy, J.N.; Wang, C.M.
The exact relationships between the de_ ections, slopes/rotations, shear forces, and bending moments of a thirdorder theory and those of the classical theory and the ? rst-order shear deformation theory for axisymmetric bending of isotropic circular plates are developed. The relationships enable one to obtain the solutions of the thirdorder theory from any known classical or ? rst-order theory solutions of axisymmetric circular plates for any set of boundary conditions and transverse loads. The relationships may also be used to develop ? nite element models of axisymmetric bending of circular plates according to the ? rst-order and third-order theories.